Analysis of Corporate Governance on Islamic Bank in Indonesia - Muhamad Nadratuzzaman Hosen; Nasimul Falah; Fitriyani Lathifah (AHKAM : Jurnal Ilmu Syariah, 2019)
This research demonstrates conceptual corporate governance (CG) which has relationship with regulations and Islamic teaching. Then, to investigate CG in Islamic Bank in Indonesia and to review law aspects and Islamic values related to rules of corporate CG in Islamic Bank in Indonesia. The study used qualitative approach using study literature and interview to analyze the implementation of corporate governance in Islamic bank in Indonesia. This study found that Islamic Banks which issued the rules of CG were not following philosophy of Islamic principles and not following strongly Islamic law and positive law. Hence, there were several fraud cases on Islamic banks inIndonesia. Islamic corporate governance in Indonesia still not find the implementation like in Malaysia. Rules of CG through regulation for Islamic bank is involving futher researher to examine the right policy. The regulation of corporate governance regulations for Islamic bank still need to be refined and turned into Islamic corporate governance standard in accordance with Islamic principles and national laws which required by Islamic bank.